ANALYSIS OF AUDIENCE RECEPTION ON YOUTUBE TOWARDS ANTI CYBERBULLYING VIDEO CAMPAIGN IN THE CYBER BULLY BY CAMEOPROJECT - Haryanti, Astrid; Ratna Sari, Siti Dewi Sri (Social Economics and Ecology International Journal, 2018)
Youtube is one of the leading sites to share videos. It also facilitates the video viewers to give comments. The research explores the video campaign entitled Cyber Bully (2016) produced by CameoProject and the authentic responses from the viewers in Youtube. The argument that the anti-cyberbullying video campaign generally creates only from victim’s perspective and how the society should encourage them. As an attempt to give a new perspective, this research shows that the victim of cyberbullying should also change himself in a positive way to contribute and socialize well in the society. Applying the concept of encoding – decoding by Stuart Hall (1993), the three categories such as dominant, negotiated and oppositional representatives can be seen from the responses of the interviewees in negotiated position. The research uses qualitative descriptive methodology; reception analysis and critical discourse analysis to determine the results by using in-depth interview with the selected representatives of three categories from encoding-decoding concept by Stuart Hall. The interviewers were compared by three categories in audience research; structural, behavioural and cultural based on primary data, aims and method. Results indicates the three viewers have the same perception of objective at the end which are to have courageous to being tough and responsible for ourselves and not being intimidated by unfairness or dominant power. All of them agreed that the Cameo Project video has delivered well the message of cyberbullying’s danger to the victims. To conclude, this phenomenon contributes to the cyber cultures in which Youtube is seen as a functional media in order to make meaning of a digital text and negotiate with the constructed cyber bullying by giving responses.